ANALISIS SWOT PENGEMBANGAN UMKM XYZ - Aulia Agung Dermawan; Dimas Akmarul Putera; Rosie Oktavia Puspita Rini; Wahyudi Ilham (JURNAL MANAJEMEN REKAYASA DAN INOVASI BISNIS, 2022)
This study aims to analyze the strategy of MSMEs in XYX. The study identifies internal and external factors of MSMEs, evaluates and analyzes them and formulates strategies to increase MSME turnover by minimizing weaknesses and threats and maximizing the use of opportunities and strengths. Data was collected through questionnaires and field interviews with MSME owners and MSME customers for data collection through SWOT analysis. The result shows 0.8 for Strict and -0.7 for Threat